Forced expiratory volume in 1-second and blood gas analysis in children during asthma attacks - Dewa Ayu Dini Primashanti; Putu Siadi Purniti; I Gusti Ayu Trisna Windiani (Paediatrica Indonesiana, 2018)
Background Asthma is the most common chronic disease in the world, with a high incidence in children. Blood gas analysis and pulmonary function test using spirometry are recommended to evaluate the degree of asthma in children. Spirometry test is non-invasive and easier to implement compared to blood gas analysis. Objective To evaluate for a possible correlation between forced expiratory volume in 1 second (FEV1) measured by spirometry test and blood gas analysis (pO2 and pCO2 levels) in children during an asthma attack. Methods This cross-sectional study was done in children with asthma attacks who were admitted to Sanglah Hospital, Denpasar, Bali, between November 2016 and April 2017. Subjects underwent spirometry tests and blood gas analyses. Potential correlations between FEV1 and pO2 and pCO2 levels were analyzed by Spearman’s correlation test. Results A total of 50 subjects, consisting of children aged 6 to 12 years, were diagnosed with asthma attacks during the study period. Subjects’ mean FEV1 level was 43.6%, mean pCO2 was 38.36 mmHg, and mean pO2 was 121.92 mmHg. There were no significant correlations between FEV1 and pCO2 level (r=0.206; P=0.152) or FEV1 and pO2 (r=0.157; P=0.277) found in this study. Conclusion FEV1 does not correlate with pCO2 and pO2 level in children during asthma attacks.